The main morphometric parameters of rat’s parathyriod glands after injection by cyclophosphanum and imunofan. - Kashchenko, S. A.; Erokhina, V. V. (Морфологія / Morphologia / Morfologìâ, 2013)
The aim of the work was determination of the morphometric parameters of rat’s parathyroid glands after application imunofan and cyclophosphanum. The study was conducted on 72 male rats with an initial weight 180 ± 10 g. The animals were divided into 4 groups. Rats of the first group were injected once by cyclophosphanumon 2,86 mg/kg. The second group of animals was injected by imunofan on 0,71 mg/kg for the 1, 3, 5, 7, 9 days. The third group of rats were injected by cyclophosphanum, then immunocorrection by imunofan was made. The fourth group was consisted of intact animals. Material was taken at 15, 30, 90 days after the last injection. The thickness, width, height, area of parathyroid glands was determed. The statistical analysis of the data was performed. After the administration of cyclophosphanum and imunofan the most significant changes of the linear parameters were identified on the 30thday. After correction by imunofan the most significant change of the linear parameters was observed on the 15th day. By 90th day the all of parametrs were approaching to the control data in all groups.